2022
DOI: 10.1097/gox.0000000000004303
|View full text |Cite
|
Sign up to set email alerts
|

Identifying US Plastic Surgery Training Programs that Effectively Establish Gender and Ethnically Diverse Faculty

Abstract: Background: Successful strategies to improve the representation of female and ethnically underrepresented in medicine (UIM) physicians among US plastic and reconstructive surgery (PRS) faculty have not been adequately explored. Accordingly, we aimed to identify programs that have had success, and in parallel gather PRS program directors’ and chiefs/chairs’ perspectives on diversity recruitment intentionality and strategies. Methods: We conducted a cross-sectional analysis of the demographic composition of fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…Among UiM groups, women comprise the majority of assistant professors and instructors, which suggests that the intersectionality of sex and race/ethnicity may further disadvantage this group relative to their male counterparts, particularly with regard to attaining higher rank and leadership positions 24 . Further investigation is warranted into the role of intersectionality as well as potential bias at the level of hiring, socioeconomic influences in career choice, lack of mentorship or sponsorship, National Institutes of Health funding disparities, systemic racism or bias, the culture of microsurgery and craniofacial surgery, and other potential causes 25–28 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among UiM groups, women comprise the majority of assistant professors and instructors, which suggests that the intersectionality of sex and race/ethnicity may further disadvantage this group relative to their male counterparts, particularly with regard to attaining higher rank and leadership positions 24 . Further investigation is warranted into the role of intersectionality as well as potential bias at the level of hiring, socioeconomic influences in career choice, lack of mentorship or sponsorship, National Institutes of Health funding disparities, systemic racism or bias, the culture of microsurgery and craniofacial surgery, and other potential causes 25–28 …”
Section: Discussionmentioning
confidence: 99%
“…24 Further investigation is warranted into the role of intersectionality as well as potential bias at the level of hiring, socioeconomic influences in career choice, lack of mentorship or sponsorship, National Institutes of Health funding disparities, systemic racism or bias, the culture of microsurgery and craniofacial surgery, and other potential causes. [25][26][27][28] There were a few important limitations to this study. Hand fellowship data were not collected because of the varied representation by orthopedic surgery residents, plastic surgery residents, and general surgery residents.…”
Section: Uim Representation In Fellowship and Academicsmentioning
confidence: 98%
“…17 Studies have shown that effective mentorship broadens residency diversity, where females and underrepresented minorities place significant importance on the race and ethnicity and sex of academic faculty members. 18 One example of a mentorship program that has been established is PREPPED, which is directed toward those who are underrepresented, come from socioeconomically disadvantaged backgrounds, or do not have a home plastic surgery residency program. 19 Additionally, distance mentorship has been trialed previously, which may be able to reach those interested in plastic surgery that do not have an established network nearby.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Recognizing the lack of diversity among medical providers, much emphasis has been made to increase efforts to address disparities in graduate medical education (GME). [14][15][16] Within plastic surgery, health disparities research has recommended interventions relating to legislation, care coordination, physician training, or patient education. 4,5 Robust analyses are still needed to both fully understand causes of disparities and effectively produce interventional efforts.…”
Section: Introductionmentioning
confidence: 99%